Parental perspective of behavior management techniques in dental treatment for their pre-school children / Ilham Wan Mokhtar ... [et al.] - Wan Mokhtar, Ilham; Jalani, Nur Fatin Faqhira; Hamid, Nur Amirah; Baharuddin, Izyan Hazwani (2019)
To evaluate parents' knowledge, acceptance and perceptions towards passive restraint, active restraint, parents separation, voice-control, tell-show-do, conscious sedation, and general anesthesia on their child during dental treatment as one of behavior management techniques in dentistry. Methods : A 32-items questionnaires constructed with seven set videos of selected behavior management techniques were developed and validated. Data were analyzed using SPSS version 22. Results : Fifty-five parents recruited. The sample consists of parents with children aged 3 - 5 years old. 98% of the parents are married and 2% are single parent. Most of the parents are degree holder. 42% of parents stated that they assist their children in tooth brushing and imply good oral home care practice. More than half of the parents have a substantial awareness of oral care as 60% of parents bring their children to the dentist. Tell-Show-Do (TSD) is the most accepted technique by the parents in dental treatment. The least accepted is General Anaesthesia. Conclusion : The parental knowledge and perception of suggested behavior management techniques are above average. Proper explanation and clarification of the technique will improve acceptance and lessen the parents' concern about their children dental treatment.